Utilization of Dried Leaf Litter as Organic Fertilizer in Talang Ilir Hamlet, Sukamoro Village, Banyuasin Regency, South Sumatra - Marlina, Neni; Zairani, Fitri Yetty; Hasani, Burlian; Khodijah, Khodijah; Vianto, Oktha (Altifani Journal: International Journal of Community Engagement, 2021)
None of the dried plant leaves in Sukamoro Village use them as organic fertilizer, instead, they are piled up as garbage and then burned.  This dry leaf litter is a problem and is considered to be very polluting to the nature conservation disturbance. If the dry leaf litter can be processed into solid organic fertilizer, it can reduce environmental pollution and is very useful in increasing plant growth and production. This organic fertilizer is easy to make and raw materials are available in the Sukamoro village.  This service aims to invite the people of Dusun Talang Ilir to use dry leaf litter as organic fertilizer. The counseling had been held in Talang Ilir Hamlet RT 03 RW 01 Sukamoro Subdistrict, Talang Kelapa District, Banyuasin Regency, South Sumatra from February 8 to March 8, 2021, with KKN Class 25 students of 2021.  The method used was the socialization of making organic fertilizer using dry leaf litter around the environment.  The people of Talang Ilir Hamlet RT 03 RW 01 Sukammoro Village want to try making organic fertilizers from dry leaf litter.